Eating the empire : food and society in eighteenth -century Britain - Bickham, Troy O. (Reaktion Books, 2020)
When students gathered in a London coffeehouse and smoked tobacco, Yorkshire women sipped sugar-infused tea or a Glasgow family ate a bowl of Indian curry, were they aware of the mechanisms of imperial rule and trade that made such goods readily available? In Eating the Empire, Troy Bickham unfolds the extraordinary role that food played in shaping Britain during the 'long' eighteenth century (c. 1660-1837), when recipes from around the world peppered a new generation of popular cookery books, and coffee, tea and sugar went from rare luxuries to some of the most ubiquitous commodities in Britain, reaching even the poorest and remotest of households. The trade in the empire's edibles underpinned the emerging consumer economy, fomenting the rise of modern retailing, visual advertising and consumer credit, and, via taxes, financed the military and civil bureaucracy that secured, governed and spread the empire.